2006
DOI: 10.1111/j.1365-2966.2006.10077.x
|View full text |Cite
|
Sign up to set email alerts
|

The activity of the 2004 Geminid meteor shower from global visual observations

Abstract: A comprehensive set of 612 h of visual meteor observations with a total of 29 077 Geminid meteors detected was analysed. The shower activity is measured in terms of the Zenithal Hourly Rate (ZHR). Two peaks are found at solar longitudes and with ZHR = 126 ± 4 and ZHR = 134 ± 4, respectively. The physical quantities of the Geminid meteoroid stream are the mass index and the spatial number density of particles. We find a mass index of s≈ 1.7 and two peaks of spatial number density 234 ± 36 and 220 ± 31 particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 9 publications
4
29
0
Order By: Relevance
“…3) of these zones. Our simulations match the observed ranges (207-210°) of solar longitude and outburst times (Trigo-Rodríguez et al 2007;Arlt et al 2008;Kero et al 2011; IMO Records) for these outburst years very well. Even though the uncertainties in semimajor axis (to directly compare with theoretical values in our calculations) of observed meteoroids from these highly successful observations are quite high (which is the typical case for all meteor observations, especially when the semimajor axis itself is high), the matching of outburst time frames and solar longitudes from these papers itself is a very effective way of comparing the orbital evolution of resonant meteoroids with real observations.…”
Section: Specific Calculationssupporting
confidence: 73%
See 4 more Smart Citations
“…3) of these zones. Our simulations match the observed ranges (207-210°) of solar longitude and outburst times (Trigo-Rodríguez et al 2007;Arlt et al 2008;Kero et al 2011; IMO Records) for these outburst years very well. Even though the uncertainties in semimajor axis (to directly compare with theoretical values in our calculations) of observed meteoroids from these highly successful observations are quite high (which is the typical case for all meteor observations, especially when the semimajor axis itself is high), the matching of outburst time frames and solar longitudes from these papers itself is a very effective way of comparing the orbital evolution of resonant meteoroids with real observations.…”
Section: Specific Calculationssupporting
confidence: 73%
“…Past observations (Millman 1936;Lovell 1954;Imoto and Hasegawa 1958;Rendtel and Betlem 1993;Dubietis 2003;Rendtel 2007;Trigo-Rodríguez et al 2007;Arlt et al 2008;Spurny and Shrbeny 2008;Kero et al 2011) of Orionids have shown enhanced meteor activity in some particular years. Previous interesting works (Rendtel 2007;Sato and Watanabe 2007) have highlighted the significance of 1:6 MMR in explaining the outburst in 2006.…”
Section: Specific Calculationsmentioning
confidence: 97%
See 3 more Smart Citations